Anti-inflammatory and analgesic effects of Streblus indicus - Xie, Yan-Qing; Huang, Jing-Yao; Chen, Yun-Xiu; Zhou, Qian; Zhou, Qi-Xiu; Yang, Zhu-Ya; Xu, Shi-Kui; Tan, Wen-Hong; Liu, Lu (Frontiers in Pharmacology, 2023)
The bark of Streblus indicus, a Dai medicine in China, has been listed in the Chinese Materia Medica as possessing hemostatic and analgesic properties. Ethnic medicine books record that its bark or leaves for the treatment of mumps and lymphoma. However, according to the literature survey, antiinflammatory and analgesic studies available for leaves and branches of S. indicus have been seldom reported so far. The current study focuses on the metabolites of S. indicus bark and leaves responsible for anti-inflammatory and analgesic effects on the basis of bioactive-included acetic acid writhing, hot-plate, and xylene-induced ear swelling. The secretion of inflammatory mediators, TNF-α, IL-6, IL-1β, IL-4, and IL-10, were evaluated for their anti-inflammatory by xylene-induced in mouse ear cells. Histological examination was used to assess the anti-inflammatory and analgesic effects of the branches and leaves of S. indicus, and Western blot analysis determined the mechanism of the methanolic extract of branches and leaves. Different metabolites of S. indicus significantly alleviated analgesic and anti-inflammatory effects, with no discernable differences among them. All metabolites decreased the levels of TNF-α, IL-1β, and IL-6 and increased the levels of IL-4 and IL-10. The analgesic and anti-inflammatory mechanism of the methanolic extract was related to the NF-kB signaling pathway. These results not only would account for scientific knowledge for the traditional application of S. indicus, but also provide a credible theoretical foundation for the further development of anti-inflammatory and analgesic agents.